Composite titanium dioxide and preparation method thereof

By modifying titanium dioxide and dry mixed grinding, composite titanium dioxide with excellent performance was prepared, which solved the problems of environmental pollution, poor stability and high cost in the existing titanium dioxide production process, and met the needs of high-end fields.

CN119708889AInactive Publication Date: 2025-03-28HENAN MOJING NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411903585.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing titanium dioxide production process has problems such as environmental pollution, poor product stability, high cost and susceptibility to extreme environments, and its use in food, medicine and other industries is restricted.

Method used

By modifying the rutile titanium dioxide and nanotitanium dioxide, composite titanium dioxide is prepared by dry mixed grinding. The modification treatment includes steps such as ultrasonic dispersion, cold plasma treatment and ultrafine crushing.

Benefits of technology

The prepared composite titanium dioxide particles are uniform, have good dispersed fluidity and performance stability, and have excellent whiteness, hiding power, oil absorption and photocatalytic oxidation effects, which can meet the parameter requirements of high-end demand fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708889A_ABST
    Figure CN119708889A_ABST
Patent Text Reader

Abstract

The invention discloses composite titanium dioxide and a preparation method thereof, and belongs to the technical field of titanium dioxide production.The composite titanium dioxide and the preparation method thereof are characterized in that rutile titanium dioxide and nanometer titanium dioxide are modified respectively, and then the composite titanium dioxide is prepared in a dry mixing and grinding mode; the composite titanium dioxide has the advantages of uniform particles, good dispersion fluidity, stable performance, excellent whiteness, excellent covering power, excellent oil absorbency, excellent photocatalytic oxidation effect and the like, and meets the requirements of high-end demand fields on titanium dioxide parameters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium dioxide production, and specifically relates to a composite titanium dioxide and a preparation method thereof. Background Art

[0002] Titanium dioxide is an important inorganic chemical pigment, the main component of which is titanium dioxide. There are two production processes for titanium dioxide: sulfuric acid process and chlorination process. It has important uses in industries such as coatings, inks, papermaking, plastics and rubber, chemical fibers, and ceramics.

[0003] Titanium dioxide production mainly adopts the sulfuric acid process, which consumes a large amount of ilmenite, sulfuric acid and water, and produces a variety of by-products that cause environmental pollution. In addition, titanium dioxide is often in a state of agglomeration due to its fine particles and surface forces, which makes it difficult to effectively use it when applied. In addition, the current titanium dioxide production process is complicated and costly, and it is easy to absorb moisture in the air and agglomerate, which not only affects the storage and transportation of the product, but may also have an adverse effect on the use of the product. Due to the uneven distribution of particle size, the product stability is very poor. It may be affected under extreme environmental conditions (such as strong acid or strong alkaline environment). In certain specific fields, such as food, medicine and other industries, its use is subject to certain restrictions due to its possible safety hazards. Practice has shown that the above-mentioned resources, environment and cost price issues have seriously restricted and hindered the development of titanium dioxide.

[0004] Based on this, we proposed a composite titanium dioxide and a preparation method thereof, hoping to solve the deficiencies in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a composite titanium dioxide and a preparation method thereof in view of the existing problems.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing composite titanium dioxide comprises the following steps:

[0008] S1. Mix rutile titanium dioxide and anhydrous ethanol in a mass volume ratio of 1 g: 18-26 mL, add allyl methyl dimethoxy silane after ultrasonic dispersion, continue ultrasonic dispersion for 10-16 min, add to the reactor, add chitosan cellulose and glycerol to the reactor, react at 90-98° C. for 5-7 h, filter, dry in a vacuum drying oven to constant weight, grind to obtain modified rutile titanium dioxide for later use;

[0009] S2, placing the rutile titanium dioxide obtained in step S1 in a DBD cold plasma device for cold plasma treatment, and after the treatment, the modified rutile titanium dioxide is obtained for standby use;

[0010] S3, nano titanium dioxide and deionized water are mixed in a ratio of 5-10 mg: 1L, and after ultrasonic dispersion is uniform, tannic acid, polyethylene glycol and soybean lecithin are added in sequence, and after ultrasonic dispersion and mixing, the mixture is stirred at 70-80° C. for 1-2 h, and then washed by vacuum filtration and washing. Finally, the washed product is placed in a vacuum drying oven and dried to constant weight, and then ultrafinely ground to obtain modified nano titanium dioxide for standby use;

[0011] S4, placing the modified rutile titanium dioxide obtained in step S2 and the modified nano titanium dioxide obtained in step S3 in a grinder at a mass ratio of 1:3-5 for grinding, and obtaining composite titanium dioxide.

[0012] Preferably, the mass ratio of allylmethyldimethoxysilane to rutile titanium dioxide in step S1 is 1:0.6-0.8.

[0013] Preferably, the mass ratio of rutile titanium dioxide to chitosan cellulose in step S1 is 1:0.1-0.2;

[0014] The mass ratio of the rutile titanium dioxide to glycerol is 1:0.3-0.36.

[0015] Preferably, the drying temperature in step S1 is 40-50°C.

[0016] Preferably, the power of the cold plasma treatment in step S2 is 2-4 kW, and the number of treatments is 7-11 times.

[0017] Preferably, the mass ratio of nano titanium dioxide to tannic acid in step S3 is 1:0.3-0.6;

[0018] The mass ratio of the tannic acid, polyethylene glycol and soybean lecithin is 1:1.2-1.8:8-10.

[0019] Preferably, the drying temperature in step S3 is 40-50°C.

[0020] Preferably, the technical parameters of the ultrafine grinding described in step S3 are 20000-30000 rpm, and the grinding time is 10-20 min.

[0021] Preferably, the grinding speed in step S4 is 1000-2000 rpm, and the grinding time is 20-40 min.

[0022] The composite titanium dioxide prepared by the above-mentioned method for preparing composite titanium dioxide is also within the protection scope of the present invention.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] The present invention provides a composite titanium dioxide and a preparation method thereof. The composite titanium dioxide is prepared by modifying rutile titanium dioxide and nano titanium dioxide respectively and then mixing and grinding the composite titanium dioxide by a dry method. The composite titanium dioxide has uniform particles, good dispersion fluidity, stable performance, excellent whiteness, hiding power, oil absorption, photocatalytic oxidation effect and other properties, and meets the requirements of high-end demand fields for titanium dioxide parameters.

[0025] The invention not only provides a concept of composite titanium dioxide and a preparation method thereof, but also provides a preparation method of modified rutile titanium dioxide and modified nano titanium dioxide for the chemical industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a graph comparing the photocatalytic methyl orange performance of Example 2 and various comparative examples of the specific implementation method of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A method for preparing composite titanium dioxide comprises the following steps:

[0030] S1. Mix rutile titanium dioxide and anhydrous ethanol in a mass-to-volume ratio of 1 g:18 mL, and after ultrasonic dispersion, add allylmethyldimethoxysilane in an amount of 0.6 times the mass of rutile titanium dioxide, continue ultrasonic dispersion for 10 min, and then add to a reactor, add chitosan cellulose in an amount of 0.1 times the mass of rutile titanium dioxide and glycerol in an amount of 0.3 times the mass of rutile titanium dioxide to the reactor, react at 90° C. for 5 h, filter, and then dry in a vacuum drying oven at 40° C. to constant weight, and then grind to obtain modified rutile titanium dioxide for standby use;

[0031] S2, placing the rutile titanium dioxide obtained in step S1 in a DBD cold plasma device at 2kW for 7 times, and after completion, obtaining the modified rutile titanium dioxide for standby use;

[0032] S3, nano titanium dioxide and deionized water are mixed in a ratio of 5mg:1L, and after ultrasonic dispersion is uniform, tannic acid, polyethylene glycol, and soybean lecithin are added in sequence in a mass ratio of 1:1.2:8, and after ultrasonic dispersion and mixing, the mixture is stirred at 70°C for 1h and then washed by vacuum filtration and washing. Finally, the washed product is placed in a vacuum drying oven at 40°C and dried to constant weight, and then ultrafinely ground at 20000rpm for 10min to obtain modified nano titanium dioxide for standby use;

[0033] The mass ratio of the nano titanium dioxide to tannic acid is 1:0.3;

[0034] S4. The modified rutile titanium dioxide obtained in step S2 and the modified nano titanium dioxide obtained in step S3 are placed in a grinder at a mass ratio of 1:3 and ground at 1000 rpm for 20 minutes to obtain composite titanium dioxide.

[0035] Example 2

[0036] A method for preparing composite titanium dioxide comprises the following steps:

[0037] S1. Mix rutile titanium dioxide and anhydrous ethanol in a mass-to-volume ratio of 1 g: 22 mL, and after ultrasonic dispersion, add allylmethyldimethoxysilane in an amount of 0.7 times the mass of rutile titanium dioxide, continue ultrasonic dispersion for 13 min, and then add to a reactor, add chitosan cellulose in an amount of 0.15 times the mass of rutile titanium dioxide and glycerol in an amount of 0.33 times the mass of rutile titanium dioxide to the reactor, react at 94° C. for 6 h, filter, and then dry in a vacuum drying oven at 45° C. to constant weight, and then grind to obtain modified rutile titanium dioxide for standby use;

[0038] S2, placing the rutile titanium dioxide obtained in step S1 in a DBD cold plasma device at 3kW for 9 times, and after completion, obtaining the modified rutile titanium dioxide for standby use;

[0039] S3, nano titanium dioxide and deionized water are mixed in a ratio of 7.5mg:1L, and after ultrasonic dispersion is uniform, tannic acid, polyethylene glycol, and soybean lecithin are added in sequence in a mass ratio of 1:1.5:9, and after ultrasonic dispersion and mixing, the mixture is stirred at 75°C for 1.5h and then washed by vacuum filtration and washing. Finally, the washed product is placed in a vacuum drying oven at 45°C and dried to constant weight, and then ultrafinely ground at 25000rpm for 15min to obtain modified nano titanium dioxide for standby use;

[0040] The mass ratio of the nano titanium dioxide to tannic acid is 1:0.45;

[0041] S4. The modified rutile titanium dioxide obtained in step S2 and the modified nano titanium dioxide obtained in step S3 are placed in a grinder at a mass ratio of 1:4 and ground at 1500 rpm for 30 min to obtain composite titanium dioxide.

[0042] Example 3

[0043] A method for preparing composite titanium dioxide comprises the following steps:

[0044] S1. Mix rutile titanium dioxide and anhydrous ethanol in a mass-to-volume ratio of 1 g: 26 mL, and after ultrasonic dispersion, add allylmethyldimethoxysilane in an amount of 0.8 times the mass of rutile titanium dioxide, continue ultrasonic dispersion for 16 min, and then add to a reactor, add chitosan cellulose in an amount of 0.2 times the mass of rutile titanium dioxide and glycerol in an amount of 0.36 times the mass of rutile titanium dioxide to the reactor, react at 98° C. for 7 h, filter, and then dry in a vacuum drying oven at 50° C. to constant weight, and then grind to obtain modified rutile titanium dioxide for standby use;

[0045] S2, placing the rutile titanium dioxide obtained in step S1 in a DBD cold plasma device at 4kW for 11 times, and after completion, obtaining the modified rutile titanium dioxide for standby use;

[0046] S3, nano titanium dioxide and deionized water are mixed in a ratio of 10mg:1L, and after ultrasonic dispersion is uniform, tannic acid, polyethylene glycol, and soybean lecithin are added in a mass ratio of 1:1.8:10 in sequence, and after ultrasonic dispersion and mixing, the mixture is stirred at 80°C for 2h and then washed by vacuum filtration and washing. Finally, the washed product is placed in a vacuum drying oven at 50°C and dried to constant weight, and then ultrafinely ground at 30000rpm for 20min to obtain modified nano titanium dioxide for standby use;

[0047] The mass ratio of the nano titanium dioxide to tannic acid is 1:0.6;

[0048] S4. The modified rutile titanium dioxide obtained in step S2 and the modified nano titanium dioxide obtained in step S3 are placed in a grinder at a mass ratio of 1:5 and ground at 2000 rpm for 40 minutes to obtain composite titanium dioxide.

[0049] Comparative Example 1

[0050] A method for preparing composite titanium dioxide comprises the following steps:

[0051] S1, nano titanium dioxide and deionized water were mixed in a ratio of 7.5mg:1L, and after ultrasonic dispersion was uniform, tannic acid, polyethylene glycol, and soybean lecithin were added in sequence in a mass ratio of 1:1.5:9, and after ultrasonic dispersion and mixing, the mixture was stirred at 75°C for 1.5h and then washed by vacuum filtration and washing. Finally, the washed product was placed in a vacuum drying oven at 45°C and dried to constant weight, and then ultrafinely ground at 25000rpm for 15min to obtain modified nano titanium dioxide for standby use;

[0052] The mass ratio of the nano titanium dioxide to tannic acid is 1:0.45;

[0053] S2. Put the rutile titanium dioxide and the modified nano titanium dioxide obtained in step S1 in a grinder at a mass ratio of 1:4 and grind them at 1500 rpm for 30 minutes to obtain composite titanium dioxide.

[0054] Comparative Example 2

[0055] A method for preparing composite titanium dioxide comprises the following steps:

[0056] S1. Mix rutile titanium dioxide and anhydrous ethanol in a mass-to-volume ratio of 1 g: 22 mL, and after ultrasonic dispersion, add allylmethyldimethoxysilane in an amount of 0.7 times the mass of rutile titanium dioxide, continue ultrasonic dispersion for 13 min, and then add to a reactor, add chitosan cellulose in an amount of 0.15 times the mass of rutile titanium dioxide and glycerol in an amount of 0.33 times the mass of rutile titanium dioxide to the reactor, react at 94° C. for 6 h, filter, and then dry in a vacuum drying oven at 45° C. to constant weight, and then grind to obtain modified rutile titanium dioxide for standby use;

[0057] S2, placing the rutile titanium dioxide obtained in step S1 in a DBD cold plasma device at 3kW for 9 times, and after completion, obtaining the modified rutile titanium dioxide for standby use;

[0058] S4. The modified rutile titanium dioxide and nano titanium dioxide obtained in step S2 are placed in a grinder at a mass ratio of 1:4 and ground at 1500 rpm for 30 min to obtain composite titanium dioxide.

[0059] Comparative Example 3

[0060] A method for preparing composite titanium dioxide comprises the following steps:

[0061] Rutile titanium dioxide and nano titanium dioxide were placed in a grinder at a mass ratio of 1:4 and ground at 1500 rpm for 30 minutes to obtain composite titanium dioxide.

[0062] test

[0063] The hiding power of composite titanium dioxide was determined according to GB 1709-1979; the oil absorption was determined according to GB 1712-1979; the whiteness was determined according to YQ-Z-48A whiteness meter.

[0064] The test results are shown in Table 1 below:

[0065] Table 1 Performance comparison of composite titanium dioxide in various embodiments and comparative examples

[0066]

[0067]

[0068] It can be seen from Table 1 above that the composite titanium dioxide prepared by the method of the present application has significant advantages in hiding power, oil absorption, whiteness and other properties, and has excellent comprehensive performance, which can meet the requirements of high-end demand areas for titanium dioxide parameters.

[0069] In order to further compare the technical effect of the present invention, the photocatalytic performance of the composite titanium dioxide was evaluated by the degradation of methyl orange under ultraviolet light. The absorbance of the degraded methyl orange solution was measured using a Lambda 750 UV-visible spectrophotometer from PE Company of the United States, and the absorbance was measured at a fixed wavelength of 464nm. The methyl orange concentration (C) in the solution was then obtained through the relationship between absorbance and concentration. The degradation effect of the sample was judged by the change in C / C0. Using C t Calculate the degradation rate D of methyl orange at time t, the formula is as follows:

[0070]

[0071] Where: C0 and C t represent the concentrations of methyl orange solution at reaction time 0 and t, respectively.

[0072] The results are as follows Figure 1 As shown:

[0073] Depend on Figure 1 It can be seen that after 30 minutes of dark reaction, the concentration of methyl orange solution was slightly reduced under the action of composite titanium dioxide, indicating that composite titanium dioxide has a strong adsorption effect on the degraded products and can improve the photocatalytic activity.

[0074] Comparing Comparative Examples 1 to 3 with Example 2, it can be seen that with the increase of illumination time, the composite titanium dioxide of Example 2 has a strong degradation effect on methyl orange, and the degradation rate reaches 98% after 20 minutes, and the photocatalytic effect is obvious.

[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a composite titanium dioxide, characterized in that: The steps include: S1. Mix rutile titanium dioxide and anhydrous ethanol in a mass volume ratio of 1 g: 18-26 mL, add allyl methyl dimethoxy silane after ultrasonic dispersion, continue ultrasonic dispersion for 10-16 min, add to the reactor, add chitosan cellulose and glycerol to the reactor, react at 90-98° C. for 5-7 h, filter, dry in a vacuum drying oven to constant weight, grind to obtain modified rutile titanium dioxide for later use; S2, placing the rutile titanium dioxide obtained in step S1 in a DBD cold plasma device for cold plasma treatment, and after the treatment, the modified rutile titanium dioxide is obtained for standby use; S3, nano titanium dioxide and deionized water are mixed in a ratio of 5-10 mg: 1L, and after ultrasonic dispersion is uniform, tannic acid, polyethylene glycol and soybean lecithin are added in sequence, and after ultrasonic dispersion and mixing, the mixture is stirred at 70-80° C. for 1-2 h, and then washed by vacuum filtration and washing. Finally, the washed product is placed in a vacuum drying oven and dried to constant weight, and then ultrafinely ground to obtain modified nano titanium dioxide for standby use; S4, placing the modified rutile titanium dioxide obtained in step S2 and the modified nano titanium dioxide obtained in step S3 in a grinder at a mass ratio of 1:3-5 for grinding, and obtaining composite titanium dioxide.

2. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The mass ratio of allylmethyldimethoxysilane to rutile titanium dioxide in step S1 is 1:0.6-0.

8.

3. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The mass ratio of rutile titanium dioxide to chitosan cellulose in step S1 is 1:0.1-0.2; The mass ratio of the rutile titanium dioxide to glycerol is 1:0.3-0.

36.

4. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The drying temperature in step S1 is 40-50°C.

5. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The power of the cold plasma treatment in step S2 is 2-4 kW, and the number of treatments is 7-11 times.

6. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The mass ratio of nano titanium dioxide to tannic acid in step S3 is 1:0.3-0.6; The mass ratio of the tannic acid, polyethylene glycol and soybean lecithin is 1:1.2-1.8:8-10.

7. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The drying temperature in step S3 is 40-50°C.

8. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The technical parameters of the ultrafine grinding described in step S3 are 20000-30000 rpm and the grinding time is 10-20 min.

9. The method for preparing a composite titanium dioxide according to claim 1, characterized in that: The grinding speed in step S4 is 1000-2000 rpm, and the grinding time is 20-40 min.

10. The composite titanium dioxide prepared by the method for preparing the composite titanium dioxide according to any one of claims 1 to 9.